Introduction to the Debate on Pioneers of Capitalism - Blondé, Bruno; Spliet, Bas (TSEG - The Low Countries Journal of Social and Economic History, 2024)
On 30 June 2023, the Centre for Urban History at the University of Antwerp, the Posthumus Institute, and the Antwerp Interdisciplinary Platform for Research into Inequality hosted a workshop dedicated to Pioneers of Capitalism. The Netherlands 1000-1800, a book by Maarten Prak and Jan Luiten van Zanden published by Princeton University Press in 2022. Participants in the workshop were challenged to reflect on the broader geographical applicability of the ‘coordinated market’ variety of capitalism that Prak and Van Zanden see emerging in the Dutch Republic after the Fall of Antwerp in 1585. Both during the workshop and in this special issue, the participants engaged in a lively, stimulating discussion with the authors of Pioneers in Capitalism.